Analisis Waste Waktu Tunggu Rawat Jalan di Poli Penyakit Dalam Dengan Metode Lean Six Sigma - Artati Murwaningrum; Agus Hadian Rahim; Purwadhi Purwadhi; Nining Handayani (Journal of Innovative and Creativity, 2026)
Outpatient waiting time is a critical indicator of healthcare service quality; however, empirical realities often exceed national standards. This study aims to analyze the anatomy of operational inefficiencies (waste) within the BPJS patient service flow at the Internal Medicine Clinic of Pena 98 Hospital using the Lean Six Sigma framework. A qualitative case study methodology was employed, adopting the Define and Measure stages of the DMAIC cycle. Data collection involved Gemba Walks, in-depth interviews with 5 patients and 7 internal informants, and analysis of October 2025 queue data using NVivo 15 software. Findings indicate that 90.42% of patients experienced waiting times >60 minutes, violating the standards set by Ministry of Health Regulation (Permenkes) No. 30 of 2022. Value Stream Mapping analysis revealed a remarkably low Process Cycle Efficiency (PCE) of 4.6%, with 95.4% of patient time spent on Non-Value Added activities. Eight types of waste (DOWNTIME) were identified, with Overprocessing (redundancy between manual and digital recording) and Waiting (doctor tardiness) as the primary contributors. The study concludes that inefficiencies are systemic and require strategic interventions, including total digital transformation (paperless), the implementation of doctor performance dashboards, and facility layout re-engineering to minimize patient movement.